Stress and Deformation Analysis of Ramshorn Hook with Various Cross Sections - Bhagel Singh, Prabhat Singh (International Journal of Advanced Science and Technology, 2020)
Ramshorn hooks is a highly significant part used for lifting more loads in weighty duty industries, industries, marine transportation with using of chains, links etc. Ramshorn hooks are designed and manufactured for deliver maximum performance with no failure. The failure of Ramshorn hook mainly depends upon many factors such as geometric features, overload and its material properties. In present study material properties of hook are kept constant though cross sectional shape id different. The various cross sections used in this paper are trapezoidal, rectangular and triangular and the area of its critical cross section remains constant as outcome of cross sectional contour on stress induced is analysed. The cross sections which give minimum stress under given load is taken as the best shape. The geometry of Ramshorn hook has been created using SolidWorks. The study of stress analysis of Ramshorn hook performed using ANSYS 15 workbench. Normal stress, deformation and strain are measured only along y direction. It is found that trapezoidal cross section on given area and loads having minimum stress.